Electrocardiographic findings in a group of physically active young adults who reside at 2,600 meters above the sea level: an exploratory study - Jaime Tomás Rojas-Valencia; Elkin Higuera-Dagovett; Rodolfo Vega Llamas; Laura del Pilar Prieto Mondragón; Jorge Enrique Buitrago Espitia; Jeansy Alonso Rodríguez Buitrago (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Purpose: The physiological adaptations to regular physical activity and hypobaric hypoxia associated with high-altitude residence are related to a series of cardiovascular adaptations that can generate electrocardiographic modifications. This study aimed to describe the principal findings and determine the mean values of the electrocardiographic parameters in a group of physically active young adults who reside at a high altitude. Methods: 49 young, physically active subjects (11 women) in a Sports Sciences program participated in the study. Each participant was subjected to a medical interview, a physical examination, and a resting electrocardiogram. Two physicians analyzed the electrocardiogram, searching for criteria of anatomical or physiological abnormalities; a descriptive analysis of the duration of waves and intervals and the amplitude of the T and P waves was also carried out. Results: The mean values of the electrocardiographic parameters were between the expected values. The principal findings involve sinus bradycardia and changes associated with the right side of the heart: incomplete right bundle branch block, right QRS axis deviation, and right ventricular hypertrophy. Conclusions: The findings of this study are related to other studies that describe changes in the right side of the heart in inhabitants of high altitude and sinus bradycardia in physically active subjects and, in some cases, in high-altitude residents. Every young dweller of the altitude who engages in physical activity should be submitted to a resting ECG, considering there is a high probability of finding asymptomatic changes in the ECG that could require further exploration.